Community Experiences in Confronting Economic Inequality and Its Impacts on Livelihoods - Hot Martua Sinaga; Wargo; Kuswanto (Zabags Qu Publish, 2025)
This study aims to provide an in-depth understanding of community experiences in confronting economic inequality and the effects on social, psychological, and livelihood dimensions among low-income groups. Grounded in the observed widening gaps in wealth distribution and unequal access to economic resources in Indonesia, the research adopts a qualitative case study approach employing in-depth interviews and participant observation with individuals and groups directly affected by inequality. Findings reveal that economic inequality constrains access to education, healthcare, and decent employment, while also elevating psychological stress and social marginalization. Communities enact two primary adaptive strategies: problem-focused coping, through income diversification, micro-entrepreneurship, and stricter household resource management; and emotion-focused coping, through strengthened spiritual practices and mutual social support. By integrating perspectives on inequality, social mobility, and coping, the study contributes to theoretical refinement regarding adaptive responses to structural disadvantage and enriches the literature on lived strategies of resilience. Practically, the results inform more inclusive social policy design that centers community experiences and supports capacity-building rather than solely providing short-term material assistance.